2007
DOI: 10.1128/aem.00677-06
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Candida tropicalis by Irradiation with a He-Ne Laser To Increase Its Ability To Degrade Phenol

Abstract: Candida tropicalis isolated from acclimated activated sludge was used in this study. Cell suspensions with 5 ؋ 10 7 cells ml ؊1 were irradiated by using a He-Ne laser. After mutagenesis, the irradiated cell suspension was diluted and plated on yeast extract-peptone-dextrose (YEPD) medium. Plates with approximately 20 individual colonies were selected, and all individual colonies were harvested for phenol biodegradation. The phenol biodegradation stabilities for 70 phenol biodegradation-positive mutants, mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…In this study, the emphasis was laid on its ability to utilize phenol as a sole carbon and energy source. It has been reported that the fungal metabolism of aromatic compounds occur via orthoWssion pathway [1,7]. The phenol hydroxylase (EC 1.14.13.7) and cis,cis-muconate lactonase (EC 5.5.1.1) are key enzymes in this catabolic process.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the emphasis was laid on its ability to utilize phenol as a sole carbon and energy source. It has been reported that the fungal metabolism of aromatic compounds occur via orthoWssion pathway [1,7]. The phenol hydroxylase (EC 1.14.13.7) and cis,cis-muconate lactonase (EC 5.5.1.1) are key enzymes in this catabolic process.…”
Section: Resultsmentioning
confidence: 99%
“…Cell density was monitored spectrophotometrically by measuring the optical density at 600 nm [27]. Inorganic impurity in oil was determined by the standard Petroleum Products and Additives-Determination of Mechanical Impurities-Gravimetric Method (GB/T 511-2010).…”
Section: Methodsmentioning
confidence: 99%
“…The irradiation condition was varied by adjusting output power (15 mW) and exposure time (5, 10, 15, 20, 25 and 30 min) (Kohli and Gupta, 2003). The laser output power was set to 15 mW and 0.2 ml of bacterial suspension was placed in sterile test tubes and located at 30 cm under the laser for different laser exposure time (Jiang et al, 2007). After mutagenesis, bacterial suspension with serial dilutions was prepared, and three 0.1 ml parallel samples were taken out from each dilution.…”
Section: He-ne Laser Irradiation Proceduresmentioning
confidence: 99%